In vitro wound healing improvement by low-level laser therapy application in cultured gingival fibroblasts - Basso, Fernanda G.; Pansani, Taisa N. [UNESP]; Turrioni, Ana Paula S. [UNESP]; Bagnato, Vanderlei S.; Hebling, Josimeri [UNESP]; De Souza Costa, Carlos A. [UNESP] (Hindawi, 2012)
The aim of this study was to determine adequate energy doses using specific parameters of LLLT to produce biostimulatory effects on human gingival fibroblast culture. Cells (3 10 4 cells/cm 2) were seeded on 24-well acrylic plates using plain DMEM supplemented with 10 fetal bovine serum. After 48-hour incubation with 5 CO2 at 37C, cells were irradiated with a InGaAsP diode laser prototype (LASERTable; 780 3 nm; 40mW) with energy doses of 0.5, 1.5, 3, 5, and 7J/cm 2. Cells were irradiated every 24h totalizing 3 applications. Twenty-four hours after the last irradiation, cell metabolism was evaluated by the MTT assay and the two most effective doses (0.5 and 3J/cm 2) were selected to evaluate the cell number (trypan blue assay) and the cell migration capacity (wound healing assay; transwell migration assay). Data were analyzed by the Kruskal-Wallis and Mann-Whitney nonparametric tests with statistical significance of 5. Irradiation of the fibroblasts with 0.5 and 3J/cm 2 resulted in significant increase in cell metabolism compared with the nonrradiated group (P 0.05). Both energy doses promoted significant increase in the cell number as well as in cell migration (P 0.05). These results demonstrate that, under the tested conditions, LLLT promoted biostimulation of fibroblasts in vitro. Copyright © 2012 Fernanda G. Basso et al.